Hőkezelési folyamat számítógépes modellezése - Fabulya, Zoltán; Hampel, György (Jelenkori Társadalmi és Gazdasági Folyamatok, 2009)
The heat treatment of cans, particularly canned meat, is a process with a big energy need, since the cans need sterilization, a heat treatment with a long time span around 120°C with the use of fuel gas in big quantity. The reduction of the use of the natural resources is the challenge in our days which appears in the new system approach of the environment management, the principle of sustainable development. That is to say, let us produce the same amount of products with less energy consumption, or more amounts with less specific energy consumption. The heat treatment is used to avert microbiological danger. The operation regulation has to be defined in a way which produces a microbiologically reliable product, but does not harm its organoleptic peculiarities, substance, taste and flavour because of the oversized treatment. In the interest of safety we have to define the extent and the time span of the heat effect leading to the destruction of the microbiological pathogens with the use of engineering calculations, modelling and computer simulation. We also have to secure the observance of the regulations obtained this way for the sake of the higher quality and the less resource utilization. This observance ability is answered with the help of our developed model for the computer simulation of heat treatment processes.